Teori Psikologis Perilaku Dalam Analisis Pungutan Liar Di Indonesia - Cartisa Salsabila; Rahma Kurnia; Sandrina Nazwa Salsabila (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This study aims to analyze the psychological behavior related to bribery in Indonesia. The study uses a qualitative and quantitative approach to collect data from various sources, including interviews with bribe takers, the public, and law enforcement officials. The results show that the psychological behavior of bribe takers consists of several factors, such as the desire for material gain, the need for status and prestige, and the inability to cope with social pressure. The study also shows that this psychological behavior can be changed by using appropriate psychological approaches, such as cognitive therapy and behavioral therapy.